Three Weeks Versus Six Weeks of Antibiotic Therapy for Diabetic Foot Osteomyelitis: A Prospective, Randomized, Noninferiority Pilot Trial. (26th November 2020) - Gariani, Karim; Pham, Truong-Thanh; Kressmann, Benjamin; Jornayvaz, François R; Gastaldi, Giacomo; Stafylakis, Dimitrios; Philippe, Jacques; Lipsky, Benjamin A; Uçkay, lker
Abstract: Background: In patients with diabetic foot osteomyelitis (DFO) who underwent surgical debridement, we investigated whether a short (3 weeks) duration compared with a long (6 weeks) duration of systemic antibiotic treatment is associated with noninferior results for clinical remission and adverse events (AEs). Methods: In this prospective, randomized, noninferiority pilot trial, we randomized (allocation 1:1) patients with DFO after surgical debridement to either a 3-week or a 6-week course of antibiotic therapy. The minimal duration of follow-up after the end of therapy was 2 months. We compared outcomes using Cox regression and noninferiority analyses (25% margin, power 80%). Results: Among 93 enrolled patients (18% females; median age 65 years), 44 were randomized to the 3-week arm and 49 to the 6-week arm. The median number of surgical debridements was 1 (range, 0–2 interventions). In the intention-to-treat (ITT) population, remission occurred in 37 (84%) of the patients in the 3-week arm compared with 36 (73%) in the 6-week arm ( P = .21). The number of AEs was similar in the 2 study arms (17/44 vs 16/49; P = .51), as were the remission incidences in the per-protocol (PP) population (33/39 vs 32/43; P = .26). In multivariate analysis, treatment with the shorter antibiotic course was not significantly associated with remission (ITT population: hazard ratio [HR], 1.1 [95% confidence interval CI, .6–1.7]; PP population: HR, 0.8 [95% CI: .5–1.4]). Conclusions: In this randomized controlled pilot trial, a postdebridement systemic antibiotic therapy course for DFO of 3 weeks gave similar (and statistically noninferior) incidences of remission and AE to a course of 6 weeks. Clinical Trials Registration: NCT03615807; BASEC 2016-01008 (Switzerland). Abstract : In this prospective, randomized pilot trial investigating the duration of postdebridement antibiotic therapy for diabetic foot osteomyelitis, a short duration (3 weeks) was noninferior to long duration (6 weeks) for the outcomes of achieving clinical remission or the occurrence of antibiotic-related adverse events.